Vulnerabilities of the Neoliberal Global Food System: The Russia-Ukraine War and COVID-19 - Yildirim, Cuma; Önen, Hakkı Göker (Wiley, 2024)
The coronavirus 2019 (COVID-19) pandemic and the Russia-Ukraine war have demonstrated that the neoliberal system is unstable during global crises. In times of crisis, exporter countries adopt protectionist policies in the form of export restrictions to safeguard their local food supply and curb inflation. Consequently, low-income countries might find themselves unable to access essential food products. In this regard, the aftermath of the COVID-19 pandemic and the Russia-Ukraine war has gradually increased export restrictions, causing severe food supply disruptions. In particular, import-dependent countries cannot access essential food products and face famine. To this point, this study explores the vulnerabilities of neoliberalism when exporter countries turn to protectionism. Moreover, it asks whether food sovereignty and self-sufficiency could act as a safeguard for import-dependent states against such vulnerabilities. In doing so, the study aims to contribute to the literature by linking protectionism with export restrictions, diverging from the more common association of protectionism with solely import restrictions.
Cuma Yildirim/0009-0005-7511-3063; Önen, Hakkı Göker/0000-0001-7927-0238
Keywords: COVID-19; Food Crisis; Global Food System; Neoliberalism; Protectionism; Russia-Ukraine War